العلاقة بين تطور الجهاز المصرفي والنمو الاقتصادي: نظريا وتطبيقيا - زقرير، عادل (جامعة الشهيد حمه لخضر الوادي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2015)
قد اهتم الأدب الاقتصادي بدراسة العلاقة بين القطاع المالي والمصرفي والنمو الاقتصادي. والسبب في ذلك، أن القطاع المصرفي يمثل حجر الزاوية في العملية التنموية من خلال الخدمات الأساسية التي يؤديها في الاقتصاد، إذ يعمل كمجمع للموارد المالية من القطاعات الاقتصادية ذات الفائض ومن ثم تحويلها نحو تمويل نظيرتها ذات العجز بالشكل الذي يضمن التخصيص الأمثل للموارد، ومراقب لأعمال الشركات التي تقترض من البنوك، ومسهل للتداول، وكموفر لآلية التحوط وتنويع المخاطر. وهي الأدوار التي ينتظر منها تعظيم العائد الاقتصادي متمثلا في ارتفاع كافة المؤشرات الاقتصادية سواء على المستوى الكلي أو الجزئي. وتهدف هذه الورقة البحثية إلى حصر أهم وظائف القطاع المصرفي، والتي تؤدي إلى النمو الاقتصادي، وكما يراها (ROSS LIVINE)، ناهيك عن محاولتها حصر أهم الدراسات النظرية التي تطرقت إلى علاقة تطور القطاع المصرفي بالنمو الاقتصادي، والتي يعتبر (J. SCHUMPETER) رائدا لها، علاوة على التطرق إلى أهم الدراسات العملية (التجريبية)، والتي جاءت بعد الثورة في مجال استخدام تقنيات الاقتصاد القياسي، والتي حرصت في مجملها على تقديم الدلائل العملية على وجود علاقة سببية بين تطور القطاع المصرفي والنمو الاقتصادي.
The economic literature interested to examining the relationship between the financial and banking sector and economic growth. The reason for this , that the banking sector is a cornerstone in the development process through basic services performed in the economy , as it works as the pool of financial resources from economic sectors with a surplus and then converted to finance its counterpart with a deficit that will ensure optimal allocation of resources , and monitor the work of companies that borrow from banks , and facilitator for trading , and as a provider mechanism for hedging and risk diversification . It is the roles that are expected to maximize the economic return represented by the height of all the economic indicators both at the partial or total. The aim of this paper is to limit the most important functions of the banking sector, and that lead to economic growth, as seen by (ROSS LIVINE), not to mention trying to limit the most important theoretical studies, which touched upon the relationship of the development of the banking sector to economic growth, which is considered (J. SCHUMPETER) leading her , in addition to addressing the most important empirical studies (experimental), and that came after the revolution in the use of techniques econometrics, which is keen in its entirety to provide empirical evidence on the existence of a causal relationship between the development of the banking sector and economic growth.
Keywords: القطاع المصرفي -- النمو الاقتصادي -- الاقتصاد القياسي -- السياسة المالية